Seven new species of systaria simon, 1897 from southeast Asia (Araneae, Clubionidae, Systariinae) - Pakawin Dankittipakul (2018)
The male of Systaria cervina (Simon, 1897) is newly described; the female internal genitalia are illustrated for the first time. Seven new species are described from Southeast Asia: S. decidua sp. nov. and S. lanna sp. nov. from northern Thailand; S. insolita sp. nov. from northeastern Thailand; S. bifida sp. nov. from southern Thailand and Myanmar; S. acuminata sp. nov. from southern Thailand and Indonesia; S. convolutiva sp. nov. from Indonesia; S. deelemanae sp. nov. from the Philippines. Two additional characters are recognized among Systaria species and considered synapomorphies for the genus: the base of the cymbium on retrolateral side is provided with a sharply pointed cymbial tubercle or an elevated, oblique ridge; the anterior bursae of the internal female genitalia are distinctly sclerotized. Copyright © 2011.